Persistent Physical Symptoms as Perceptual Dysregulation: A Neuropsychobehavioral Model and Its Clinical Implications. Issue 5 (June 2018) - Henningsen, Peter; Gündel, Harald; Kop, Willem J.; Löwe, Bernd; Martin, Alexandra; Rief, Winfried; Rosmalen, Judith G.M.; Schröder, Andreas; van der Feltz-Cornelis, Christina; Van den Bergh, Omer
ABSTRACT: Objective: The mechanisms underlying the perception and experience of persistent physical symptoms are not well understood, and in the models, the specific relevance of peripheral input versus central processing, or of neurobiological versus psychosocial factors in general, is not clear. In this article, we proposed a model for this clinical phenomenon that is designed to be coherent with an underlying, relatively new model of the normal brain functions involved in the experience of bodily signals. Methods: Based on a review of recent literature, we describe central elements of this model and its clinical implications. Results: In the model, the brain is seen as an active predictive processing or inferential device rather than one that is passively waiting for sensory input. A central aspect of the model is the attempt of the brain to minimize prediction errors that result from constant comparisons of predictions and sensory input. Two possibilities exist: adaptation of the generative model underlying the predictions or alteration of the sensory input via autonomic nervous activation (in the case of interoception). Following this model, persistent physical symptoms can be described as "failures of inference" and clinically well-known factors such as expectation are assigned a role, not only in the later amplification of bodily signals but also in the very basis of symptom perception. Conclusions: We discuss therapeutic implications of such a model including new interpretations for established treatments as well as new options such as virtual reality techniques combining exteroceptive and interoceptive information.